The Influence Of Lifestyle, Financial Intelligence, And Social Environment On Financial Behavior (Survey On Students Receiving The Indonesian Smart Card Scholarship At Muhammadiyah University Sukabumi) - Nurul Jauza Putri; Tetty Sufianty zafar; Nor Norisanti (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of lifestyle, financial intelligence, and social environment on the financial behavior of students who receive Smart Indonesia Card (KIP) scholarships at the University of Muhammadiyah Sukabumi, with the hypothesis that these three variables have a significant effect on financial behavior. This study used a quantitative method with an associative approach, and involved 245 respondents who were selected through a proportionate stratified random sampling technique. Data collection was carried out through questionnaires, literature studies, and student data. The results of the study show that lifestyle, financial intelligence, and social environment each have a significant influence on financial behavior, this is highlighted by obtaining T calculation 11,468 > 1,970 T table. Financial intelligence has a significant effect on financial behavior, this is highlighted by obtaining T calculations of 9,425 > 1,970 T tables. Likewise, the social environment has a significant influence on financial behavior, this is highlighted by obtaining T calculation of 12,295 > 1,970 T tables. The implications of this study provide recommendations for scholarship managers and educational institutions to strengthen financial behavior coaching through lifestyle management, financial intelligence development, and a positive social environment.